ANALISIS POTENSI EKONOMI WILAYAH PURWOMANGGUNG (Studi di Kabupaten Purworejo, Wonosobo, Kab. Magelang, Kota Magelang, Temanggung) - Septiani, Reni Eka; Dewi, Aditya Kumala; Rahmah, Syifaur; Firdaus, Anzar Alfat (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to analyze the basic and nonbasic sectors in 17 GDP sectors in the Purwomanggung economic development area. The data used is constant price GDP data from the Central Statistics Agency (BPS). The analysis method applied is Local Quotient (LQ) analysis. The results of the study show that the Purworejo area has 9 base sectors, Wonosobo has 8 base sectors, Magelang Regency has 15 base sectors, Magelang City has 13 basic sectors, and Temanggung has 9 base sectors. The results of the research can be used as a reference for local governments in the Purwomanggung Economic Development Area to develop their regional potential to be able to meet local and external needs, improve welfare, and create a dynamic economy.